PELAKSANAAN PROGRAM PELATIHAN DAN PENGEMBANGAN KARYAWAN FRONT OFFICE DI HOTEL FURAYA KOTA PEKANBARU - Fitria A; Lilis Suriani (UIR Press, 2015)
Employee training and development programs implemented in order to reduce oreliminate the gap between the ability of employees to the desired organization, that is byincreasing knowledge and skills and change attitudes. But